5+4(t-2)+t=5(t-1)-7t

Simple and best practice solution for 5+4(t-2)+t=5(t-1)-7t equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+4(t-2)+t=5(t-1)-7t equation:


Simplifying
5 + 4(t + -2) + t = 5(t + -1) + -7t

Reorder the terms:
5 + 4(-2 + t) + t = 5(t + -1) + -7t
5 + (-2 * 4 + t * 4) + t = 5(t + -1) + -7t
5 + (-8 + 4t) + t = 5(t + -1) + -7t

Combine like terms: 5 + -8 = -3
-3 + 4t + t = 5(t + -1) + -7t

Combine like terms: 4t + t = 5t
-3 + 5t = 5(t + -1) + -7t

Reorder the terms:
-3 + 5t = 5(-1 + t) + -7t
-3 + 5t = (-1 * 5 + t * 5) + -7t
-3 + 5t = (-5 + 5t) + -7t

Combine like terms: 5t + -7t = -2t
-3 + 5t = -5 + -2t

Solving
-3 + 5t = -5 + -2t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '2t' to each side of the equation.
-3 + 5t + 2t = -5 + -2t + 2t

Combine like terms: 5t + 2t = 7t
-3 + 7t = -5 + -2t + 2t

Combine like terms: -2t + 2t = 0
-3 + 7t = -5 + 0
-3 + 7t = -5

Add '3' to each side of the equation.
-3 + 3 + 7t = -5 + 3

Combine like terms: -3 + 3 = 0
0 + 7t = -5 + 3
7t = -5 + 3

Combine like terms: -5 + 3 = -2
7t = -2

Divide each side by '7'.
t = -0.2857142857

Simplifying
t = -0.2857142857

See similar equations:

| 0.5/6(30) | | 5f+2+90=122 | | 13v+4.5=2v-1 | | 11194.21-h=17057 | | 0.5/6(0) | | -6+x=11 | | (3xy)(-4x^2y)= | | -4(2x-3)+3x=32 | | f(-1)=3(-1)-9 | | 0.25(6+8)= | | 2a-9=6a+7 | | v=1/3*12*13 | | x(y/y-x)^2 | | v=1/3*12*13 | | 7x+10=-4 | | 0.25(6+8)= | | 7x+10=-4 | | (-4x^3)=(-5x^7) | | (-4x^3)=(-5x^7) | | 0.5x=0.5x+1 | | 63=7(10-x) | | 4x+6x=15+5 | | -7m+20=#17m-10 | | 4(6+2i)=24+8i | | -4/12 | | 58+5x+10+11x+2=180 | | (7+i)+13=7+(i+13) | | 0.25(6x+8)= | | -3(1+4.5)=-17.5 | | 7p+16=-26 | | (4+i)+(-4-i)=0 | | 14xy-21xy^2= |

Equations solver categories